Anxiety and self-efficacy in Chinese international students’ L3 French learning with L2 English and L3 French - Lin, Qiuhan (Frontiers in Psychology, 2022)
The present mixed-method study explored the relationship between students’ third language anxiety (TLA) and self-efficacy in the context of combining a second language (L2) and a third language (L3) for third language acquisition. The research data were collected among 243 Chinese International students using English (L2) and French (L3) to study French (L3) at one university in the U.K. Major findings were: 1) There were four factors of TLA (i.e., Fear of negative evaluation, Communication apprehension, Fear of inadequate performance in a foreign language (FL) classroom, and Negative attitudes towards the English class) and two factors of self-efficacy (i.e., Cognitive engagement, and Behavior); 2) The level of these students’ anxiety was negatively correlated with the level of their self-efficacy in learning an L3; 3) The participants’ TLA levels contributed to the prediction of their self-efficacy levels; 4) In the interview, all three participants reported that the similarity between English and French in grammar and pronunciation rules influenced their anxiety of learning French as an L3. All of them encountered communication apprehension, and two of them proposed some coping strategies. These findings can provide educational implications for exploring the relationship between anxiety and self-efficacy among international students who use L2 and L3 to learn an L3 in a foreign country.